Sistem Informasi Penjualan Berbasis Web Menggunakan Metode Prototipe - Nurhadi Nurhadi; Novri Gusrial Can (Universitas Katolik Widya Karya Malang, 2024)
A web-based sales information system is a key element in the success of modern business, especially in the rapidly growing e-commerce era. Developing information systems that are responsive and adaptive to change is a major challenge in meeting dynamic market demands. The problem that occurs is that the web application that is built is not in accordance with the wishes and needs of the user so that applications and transactions are difficult to carry out. This article describes the implementation of the prototype method in developing a web-based sales information system, with a focus on aspects of needs analysis, design, development, implementation, and testing and evaluation. By developing a web-based sales information system with a prototype method, consumers can easily operate the application and make transactions easier because this system can be used anywhere and anytime and its development involves consumers, so this system can really be used well and easily.